The narrator in The Great Gatsby by F. Scott Fitzgerald - Fodor Edit (2001)
The Great Gatsby is considered to be F. Scott Fitzgerald’s best novel partly because of its narrative strategy. However, the character of the narrator divides the critics of The Great Gatsby. In this thesis paper, I will examine what sort of narration the author used and why it proved to be successful. I will also scrutinise the complex personality of the narrator called Nick Carraway and interpret his relationship with, and evaluation ofthe title hero called Jay Gatsby. I will present arguments for and against the acceptance of Carraway’s narration and prove the narrator’s credibility.